2016
DOI: 10.1097/dss.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

A Trial Online Educational Melanoma Program Aimed at the Hispanic Population Improves Knowledge and Behaviors

Abstract: This study provides evidence that an online educational video targeted at the Hispanic population has potential to improve melanoma awareness. This type of intervention may lead to earlier diagnosis and better prognosis for Hispanic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 13 publications
1
26
0
Order By: Relevance
“…In keeping with the recommendations provided by the ODPHP, our study results indicate that a brief, captioned video scripted at an elementary school level can be an effective method for patient instruction. These findings are consistent with prior work that has shown a benefit to video-based delivery ( Love et al, 2016 , Roman et al, 2016 , Van Acker and Kuriata, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with the recommendations provided by the ODPHP, our study results indicate that a brief, captioned video scripted at an elementary school level can be an effective method for patient instruction. These findings are consistent with prior work that has shown a benefit to video-based delivery ( Love et al, 2016 , Roman et al, 2016 , Van Acker and Kuriata, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…). From 22 included papers, detailed in Table S1 (see Supporting Information), we identified 18 included studies, as three papers reported on the same set of studies, with some reporting additional outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…More intervention studies ( n = 10) engaged in surveillance SSE practices were targeted at those of known risk due to their prior medical history or being older men, compared with focusing on screening SSE practice ( n = 8), for people at no increased risk of skin cancer, including healthy volunteers . Most studies ( n = 11) focused on SSE to detect melanoma, with the remaining ones not differentiating between melanoma and NMSC, but focusing on the detection of skin cancer or not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies showing that knowledge-based interventions, especially WWW.MDEDGE.COM/DERMATOLOGY when delivered in Spanish, improve understanding of skin cancer, personal risk, and self-examinations, and we support Ms. Torres' efforts in utilizing her platform to provide information about melanoma in Spanish. [8][9][10][11][12] Radhika Srivastava, MD; Cindy Wassef, MD; Babar K. Rao, MD…”
Section: Authors' Responsementioning
confidence: 99%